2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5334545
|View full text |Cite
|
Sign up to set email alerts
|

Reference-free automatic quality assessment of tracheoesophageal speech

Abstract: Abstract-Evaluation of the quality of tracheoesophageal (TE) speech using machines instead of human experts can enhance the voice rehabilitation process for patients who have undergone total laryngectomy and voice restoration. Towards the goal of devising a reference-free TE speech quality estimation algorithm, we investigate the efficacy of speech signal features that are used in standard telephone-speech quality assessment algorithms, in conjunction with a recently introduced speech modulation spectrum measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the context of the original feature definition, an additional noise was found to be caused by room reverberation (Falk et al, 2010). For TE speech, it was shown in (Huang et al, 2009) that these additional modulation frequencies are due to artefacts (e.g. gargling noise, raspiness) found in the voice.…”
Section: Gargling Noise/creakinessmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of the original feature definition, an additional noise was found to be caused by room reverberation (Falk et al, 2010). For TE speech, it was shown in (Huang et al, 2009) that these additional modulation frequencies are due to artefacts (e.g. gargling noise, raspiness) found in the voice.…”
Section: Gargling Noise/creakinessmentioning
confidence: 99%
“…gargling noise, raspiness) found in the voice. In (Huang et al, 2009), RSMR was observed to be the most efficient feature for the automatic estimation of the TE speech quality. Figure 6 displays, for the three datasets, the distributions of the proportion of creakiness (on a logarithmic scale) and of RSMR.…”
Section: Gargling Noise/creakinessmentioning
confidence: 99%
See 2 more Smart Citations